Strategi Komunikasi Kyai Agus Ma’arif Dalam Sosialisasi Ajaran Islam Kepada Santri Penyandang ODGJ Di Padepokan Tahfidzul Qur’an Ibnu Rusydi Jombang - Sairah, Muhammad Ikhsan; Islam, Ahmad Fakhruddin Fajrul (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
This study discusses "The Communication Strategy of Kyai Agus Ma’arif in the Socialization of Islamic Teachings to Santri Penyandang ODGJ in Padepokan Tahfidzul Qur’an Ibnu Rusydi Jombang." The aim of this research is to understand how the communication strategy process works. Agus Ma’arif, How to Socialize Islamic Teachings to the Sanhedrin of ODGJ In this research, it uses a type of qualitative research, that is, it dissects the data that has been obtained. As for the key information and the main subject of this research, it is the Communication strategy and Ma’arif. Data collection techniques are used, starting with observations, then conducting interviews, and continuing with documentation. The technical analysis of data in this study was done by means of reduction of data, presentation of data, and drawing conclusions, as well as supplemented with verification of the validity of the data. The results of the research showed that the Communication Strategy of Kyai Agus Ma’arif in the Socialization of Islamic Teachings to Santri Penyandang ODGJ in Padepokan Tahfidzul Qur’an Ibnu Rusydi Jombang went well. Kyai Agus Ma'arif's communication strategy is with all individual approaches and moral approaches because the background of extraordinary santri is a santri who has illnesses of delay, with patterns of affection and equality approaches applied that can make them conscious and heal from the disease they suffer